Model Rekonstruksi Peran Keluarga dalam Pembentukkan Karakter Religius Remaja di Era Digital - Fatimah Noor Rachma; Triono Ali Mustofa (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to formulate a model for reconstructing the family's role in shaping the religious character of adolescents in the digital era within the Paloma Regency Makamhaji housing complex. The study employs a field research method with a qualitative descriptive approach. Data were gathered through interviews with parents serving as the primary data source and supplemented by secondary data, including documents, activity records, and relevant literature. The findings indicate that the formation of adolescents' religious character is achieved through parental role modeling, open two-way communication, and the habitual practice of religious activities such as congregational prayers and joint Quran recitation. Persuasive communication patterns combined with consistent guidance proved effective in fostering religious awareness among adolescents. However, the process of religious character formation faces various challenges, such as the influence of technology and social media, parents' time constraints due to work commitments, differences of opinion with adolescents, and family economic factors. For parents, religious character is viewed as a fundamental life foundation that serves as a moral safeguard for adolescents as they navigate the changing times. Therefore, a reconstruction of the family's role is necessary emphasizing strengthened role modeling, effective communication, and continuous guidance to cultivate a generation characterized by good morals and religiosity.